Legal analysis of the provisions prohibiting marriage between female soldiers and male soldiers of lower rank in gender equality - Harjoko Simbolon (Annals of Justice and Humanity, 2024)
Purpose: This study analyzes the provisions prohibiting marriage for female soldiers with male soldiers of lower rank in the context of gender equality and human rights. Research methodology: The regulation is contained in Perpang No. 50 of 2014 and several other technical instructions in the TNI environment, a comparison with flexible Polri regulations that prioritize the principle of justice without discrimination. Results: Through a normative legal approach, this study found that this prohibition is contrary to various national and international legal instruments, such as the 1945 Constitution, Compilation of Islamic Law, Law Number 1 of 1974 concerning Marriage, Law Number 39 of 1999 concerning Human Rights, UDHR, ICCPR and CEDAW. The prohibition not only creates injustice but also affects the morale and welfare of soldiers.